PERSEPSI PETANI TERHADAP SISTEM PERTANIAN ORGANIK DAN ANORGANIK DALAM BUDIDAYA PADI SAWAH - Juliantika Juliantika; Tubagus Hasanuddin; Begem Viantimala (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The purposes of this research were to determine the performance of organic and anorganic farming systems in wetland rice cultivation, rice farmers’ perception, the related factors to farmers' perception, the differences in rice farmers’ perceptions, and the constraints faced in that applications in Pajaresuk and Pujodadi Village. The data collection was conducted in November - December 2017. The research method used was census. The number of organic and anorganic rice farmers sampled were 35 farmers. The data was analyzed by descriptive analysis, Spearman rank correlation and the Mann-Whitney test. The results of this research show that the performance of organic and anorganic rice farming were land processing, seeding, planting, pest and disease controlling, fertilizating, irrigating, and harvesting. The differences performance of organic and anorganic rice farming were in seeding, pests and diseases controlling, and fertilizing. The rice farmers' perception to organic farming systems was quite good. The related factors to farmers' perception were social interaction, community support, and farmers' interests. There were no significant differences between organic farmers’ perceptions and the anorganic farmers’ perceptions. The constraint faced in the application of organic farming system was the difficulty of maintenance in cultivation, while in the application of anorganic farming systemwas the high costs, but the selling price was relatively low. Key words: anorganic rice, organic rice, perception